2013
DOI: 10.1016/j.febslet.2012.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Protein dynamics in living cells studied by in‐cell NMR spectroscopy

Abstract: a b s t r a c tMost proteins function in cells where protein concentrations can reach 400 g/l. However, most quantitative studies of protein properties are performed in idealized, dilute conditions. Recently developed in-cell NMR techniques can provide protein structure and other biophysical properties inside living cells at atomic resolution. Here we review how protein dynamics, including global and internal motions have been characterized by in-cell NMR, and then discuss the remaining challenges and future d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 58 publications
0
38
0
1
Order By: Relevance
“…These properties are expected to result in a large number of charge-charge repulsions in cells. Indeed, it has been suggested that these repulsions are what allow GB1 to tumble freely in the cell and yield high quality in-cell 15 N-1 H HSQC spectra (13,14,54,55,67,68). These repulsive interactions enhance the volume excluded by hard interactions in cells, thus favoring the compact native state and resulting in the observed stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…These properties are expected to result in a large number of charge-charge repulsions in cells. Indeed, it has been suggested that these repulsions are what allow GB1 to tumble freely in the cell and yield high quality in-cell 15 N-1 H HSQC spectra (13,14,54,55,67,68). These repulsive interactions enhance the volume excluded by hard interactions in cells, thus favoring the compact native state and resulting in the observed stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…While structure determination of small oligomers of Ab/ inhibitor by combining simulations, solution NMR and electron-spray ionization mass-spectrometry [41 ], would represent a real breakthrough, in-cell NMR experiments on amyloid peptides alone and with inhibitors are critical because crowding can change the stability and equilibrium ensembles [42]. It is also important to take into account that the population of brain Ab oligomers changes with aging [43 ], and understand why the A2T and A2V mutations protect from AD [44 ,45].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of conformational flexibility for catalytic efficiency has promoted the development of new methodologies such as molecular dynamics and nuclear magnetic resonance that permit investigation of protein mobility at time scales of femtoseconds to seconds. 49,54 …”
Section: Catalytic Plasticitymentioning
confidence: 99%